Analysis factors acceptance of e-learning using technology acceptance model approach - Viendy Nurul Kusumawan; Eko Marpanaji (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
E-learning is one of the media in the current learning process, but many facts in the field show that the process of using it is not optimal. Many factors affect one of them, from the user's difficulty to operate it. This research aims to identify the factors that influence the use of the e-learning portal at SMK Muhammadiyah 3 Yogyakarta with a teacher and student as respondents. This research uses a quantitative approach with an ex-post-facto approach. The primary data source comes from sharing an online questionnaire (google form) which contains 30 questions using a Likert scale of 5 as an alternative answer. The research subjects were teachers of SMK Muhammadiyah 3 Yogyakarta with 69 teachers. The results showed that the use of e-learning portals by teachers and students is (1) effect by the e-learning self-efficacy factor on the e-learning portal is still not optimally successful; (2) Effect by complexity factor is still not optimally successful and (3) Effect from motivation factor is getting optimal results.